Directing the deformation paths of soft metamaterials with prescribed asymmetric units - Wu, Gaoxiang (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.